2015
DOI: 10.1164/rccm.201410-1802oc
|View full text |Cite
|
Sign up to set email alerts
|

Sex Affects Bone Morphogenetic Protein Type II Receptor Signaling in Pulmonary Artery Smooth Muscle Cells

Abstract: Rationale: Major pulmonary arterial hypertension (PAH) registries report a greater incidence of PAH in women; mutations in the bone morphogenic protein type II receptor (BMPR-II) occur in approximately 80% of patients with heritable PAH (hPAH).Objectives: We addressed the hypothesis that women may be predisposed to PAH due to normally reduced basal BMPR-II signaling in human pulmonary artery smooth muscle cells (hPASMCs). Methods:We examined the BMPR-II signaling pathway in hPASMCs derived from men and women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 44 publications
4
89
2
Order By: Relevance
“…Thus, these genes show retention of sex bias in their expression (25). Correspondingly, female-derived PASMCs proliferate modestly faster in response to 5-HT, PDGF or BMP4 (25). These observations are similar to the findings of Thangavel et al (67), who observed that GH-mediated inducibility of male-biased isoforms of cytochrome P450 was better when cultures were derived from male rats but not female rats.…”
Section: Synthesis Of the Literature On Sex Bias Mediated By The Neursupporting
confidence: 83%
See 4 more Smart Citations
“…Thus, these genes show retention of sex bias in their expression (25). Correspondingly, female-derived PASMCs proliferate modestly faster in response to 5-HT, PDGF or BMP4 (25). These observations are similar to the findings of Thangavel et al (67), who observed that GH-mediated inducibility of male-biased isoforms of cytochrome P450 was better when cultures were derived from male rats but not female rats.…”
Section: Synthesis Of the Literature On Sex Bias Mediated By The Neursupporting
confidence: 83%
“…Thus, these genes show retention of sex bias in their expression (25). Correspondingly, female-derived PASMCs proliferate modestly faster in response to 5-HT, PDGF or BMP4 (25).…”
Section: Synthesis Of the Literature On Sex Bias Mediated By The Neurmentioning
confidence: 97%
See 3 more Smart Citations